Predictive and Prognostic Biomarkers for Lung Cancer Bone Metastasis and Their Therapeutic Value - Chai, Xupeng; Yinwang, Eloy; Wang, Zenan; Wang, Zhan; Xue, Yucheng; Li, Binghao; Zhou, Hao; Zhang, Wenkan; Wang, Shengdong; Zhang, Yongxing; Li, Hengyuan; Mou, Haochen; et al. (Frontiers in Oncology, 2021)
Lung cancer is the leading cause of cancer-related death worldwide. Bone metastasis, which usually accompanies severe skeletal-related events, is the most common site for tumor distant dissemination and detected in more than one-third of patients with advanced lung cancer. Biopsy and imaging play critical roles in the diagnosis of bone metastasis; however, these approaches are characterized by evident limitations. Recently, studies regarding potential biomarkers in the serum, urine, and tumor tissue, were performed to predict the bone metastases and prognosis in patients with lung cancer. In this review, we summarize the findings of recent clinical research studies on biomarkers detected in samples obtained from patients with lung cancer bone metastasis. These markers include the following: (1) bone resorption-associated markers, such as N-terminal telopeptide(NTx) /C-terminal telopeptide(CTx), C-terminal telopeptide of type I collagen(CTx-I), tartrate-resistant acid phosphatase isoform 5b(TRACP-5b), pyridinoline(PYD), and parathyroid hormone related peptide(PTHrP); (2) bone formation-associated markers, including total serum alkaline phosphatase(ALP)/bone specific alkaline phosphatase(BAP), osteopontin(OP), osteocalcin(OS), amino-terminal extension propeptide of type I procollagen/carboxy-terminal extension propeptide of type I procollagen(PICP/PINP); (3) signaling markers, including epidermal growth factor receptor/Kirsten rat sarcoma/anaplastic lymphoma kinase (EGFR/KRAS/ALK), receptor activator of nuclear factor κB ligand/receptor activator of nuclear factor κB/osteoprotegerin (RANKL/RANK/OPG), C-X-C motif chemokine ligand 12/C-X-C motif chemokine receptor 4 (CXCL12/CXCR4), complement component 5a receptor (C5AR); and (4) other potential markers, such as calcium sensing receptor (CASR), bone sialoprotein (BSP), bone morphogenetic protein 2 (BMP2), cytokeratin 19 fragment/carcinoembryonic antigen (CYFRA/CEA), tissue factor, cell-free DNA, and long non-coding RNA. The prognostic value of these markers are also investigated. Furthermore, we listed some clinical trials targeting hotspot biomarkers in advanced lung cancer referring for their therapeutic effects.